Social factors influencing religiosity of adolescents: role of family, peers and environment (Eurasian Journal of Religious Studies, 2025)
This scholarly article meticulously investigates the myriad social determinants that indelibly shape the religious beliefs and practices of adolescents, while emphasizing the intricate and multifarious interactions among familial influences, peer associations, and the broader cultural milieu. This discourse underscores the immense importance of the family as a social system, in which parental beliefs and, especially, their particular parenting styles, deeply influence the religious identity of children in all stages of their growth. Besides that, the literature emphasizes that adolescents are greatly affected by their friends and the school environment where they study. Moreover, the paper points out that people at this stage tend to seek comfort and personal support from their social circle, which, eventually, plays a significant role in their religious development. Moreover, it examines significant effects of national and ethnic background in depth, especially in migrant families, where religion often serves as a major channel for the formation of identity and the strengthening of the bond with the community. The effects of social media are also carefully considered since this recent trend can have both positive and negative impacts on teenagers' religious views, thus adding to the overall complexity of their belief systems. As a result, the research highlights the critical need for a deep understanding of these complex and multilayered social factors since such an understanding is indispensable to appreciating the changing pattern of adolescent religiosity in the context of contemporary society.Keywords: adolescents, religion, society, factors, identity
Keywords: Keywords: adolescents, religion, society, factors, identity.